2010
DOI: 10.3109/0886022x.2010.510616
|View full text |Cite
|
Sign up to set email alerts
|

Mild acute kidney injury is associated with increased mortality after cardiac surgery in patients with eGFR < 60 mL/min/1.73 m2

Abstract: Background: A small increase in serum creatinine after cardiac surgery has been associated with increased mortality. However, it is unclear whether this association varies with baseline renal function. Methods: We retrospectively reviewed data on 1359 patients who underwent cardiac surgery over a 4-year period in two tertiary care hospitals including demographic data, comorbid conditions, and intra-and postoperative complications using a standardized form. We followed patients for 90 days postoperatively and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
1
19
0
1
Order By: Relevance
“…Although the incidence of postoperative AKI following AAA repair, and contrast-induced renal injury especially following widely performed coronary interventions has been extensively reported [6][7][8] ; however, data is limited on the incidence of AKI following peripheral endovascular and open revascularization procedures. 17 In reality, patients with symptomatic PAD are at particularly high risk for having CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the incidence of postoperative AKI following AAA repair, and contrast-induced renal injury especially following widely performed coronary interventions has been extensively reported [6][7][8] ; however, data is limited on the incidence of AKI following peripheral endovascular and open revascularization procedures. 17 In reality, patients with symptomatic PAD are at particularly high risk for having CKD.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, the causes of acute kidney injury is multifactorial, when embolization due to manipulation of wire and catheters during diagnostic or interventional endovascular procedures, hypotension, stress response, use of medications with possible nephrotoxic effects (antibiotics), all playing a significant role in addition to the effects of contrast nephropathy. Although post-procedural AKI has been mostly reported following coronary interventions and aneurysm repairs, [6][7][8] there is little data on AKI following open and endovascular revascularization for PAD.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to assess renal function by sCr variation, because slight elevations are frequently observed and have been demonstrated to be associated with mortality after cardiac surgery. 21,26,27 The diagnostic criteria of 540 Guinot et al Eur J Anaesthesiol 2015; 32:535-542 renal dysfunction have recently been revised. 22 The relevance of these criteria for the postcardiac surgery period has been confirmed by several studies.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Applying AKIN and RIFLE criteria, the mortality rate (hospital discharge or 30-day mortality) is between 3.8 and 54.4% in patients who develop CSA-AKI and increases progressively with the degree of renal impairment (table 1). Recent studies reported that even mild increases in sCr levels following cardiac surgery were associated with significant effects on mortality [19,20]. Furthermore, long-term survival was significantly different by AKI duration [13], and early recovery of renal function was associated with improved long-term survival after CSA-AKI [10].…”
Section: Epidemiologymentioning
confidence: 99%